Relationship between decreased visual acuity and physical activity time in school age children - Lee Hanna; Han Jeong-Won (Sciendo, 2021)
This study aimed to investigate the physical activity of children with decreased visual acuity, thereby providing basic data for developing strategies to enhance the physical activity of school-age children.